Ribonucleotide Reductases from Bifidobacteria Contain Multiple Conserved Indels Distinguishing Them from All Other Organisms: In Silico Analysis of the Possible Role of a 43 aa Bifidobacteria-Specific Insert in the Class III RNR Homolog - Alnajar, Seema; Khadka, Bijendra; Gupta, Radhey S. (Frontiers in Microbiology, 2017)
Bifidobacteria comprises an important group/order of bacteria whose members have widespread usage in the food and health industry due to their health-promoting activity in the human gastrointestinal tract. However, little is known about the underlying molecular properties that are responsible for the probiotic effects of these bacteria. The enzyme ribonucleotide reductase (RNR) plays a key role in all organisms by reducing nucleoside di- or tri- phosphates into corresponding deoxyribose derivatives required for DNA synthesis, and RNR homologs belonging to classes I and III are present in either most or all Bifidobacteriales. Comparative analyses of these RNR homologs have identified several novel sequence features in the forms of conserved signature indels (CSIs) that are exclusively found in bifidobacterial RNRs. Specifically, in the large subunit of the aerobic class Ib RNR, three CSIs have been identified that are uniquely found in the Bifidobacteriales homologs. Similarly, the large subunit of the anaerobic class III RNR contains five CSIs that are also distinctive characteristics of bifidobacteria. Phylogenetic analyses indicate that these CSIs were introduced in a common ancestor of the Bifidobacteriales and retained by all descendants, likely due to their conferring advantageous functional roles. The identified CSIs in the bifidobacterial RNR homologs provide useful tools for further exploration of the novel functional aspects of these important enzymes that are exclusive to these bacteria. We also report here the results of homology modelling studies, which indicate that most of the bifidobacteria-specific CSIs are located within the surface loops of the RNRs, and of these, a large 43 amino acid insert in the class III RNR homolog forms an extension of the allosteric regulatory site known to be essential for protein function. Preliminary docking studies suggest that this large CSI may be playing a role in enhancing the stability of the RNR dimer complex. The possible significances of the identified CSIs, as well as the distribution of RNR homologs in the Bifidobacteriales, are discussed.